THE EFFECT OF IMPLEMENTING ACCOUNTING INFORMATION SYSTEMS ON EMPLOYEE PERFORMANCE AT THE SERVICE OFFICE TERRAIN CITY FIRE DEPARTMENT - Harlen Silalahi; Dumariani Silalahi; Rebecca Evadine; Dina Rosmaneliana; Dianty Putri Purba (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
The purpose of this study was to determine the effect of quality, security and accounting information system support facilities on employee performance at the Office of the Medan City Fire Department.The research method used in this research is quantitative research with multiple linear regression analysis. The results showed that there was a positive and significant influence between the quality, security and supporting facilities of the accounting information system on employee performance at the Medan City Fire Prevention Service Office, with the test results for the coefficient of determination (R Square) obtained a value of 0.631 or the effect of quality, safety and supporting facilities for accounting information systems on employee performance at the Medan City Fire Department Office of 63.1%. Technology is a method for methods and processes or products resulting from the application and utilization of various scientific disciplines that generate value for fulfilling needs, continuity and improving the quality of human life